2015
DOI: 10.1021/acs.jmedchem.5b00912
|View full text |Cite
|
Sign up to set email alerts
|

Targeted γ-Secretase Inhibition To Control the Notch Pathway in Renal Diseases

Abstract: Notch is a membrane inserted protein activated by the membrane-inserted γ-secretase proteolytic complex. The Notch pathway is a potential therapeutic target for the treatment of renal diseases but also controls the function of other cells, requiring cell-targeting of Notch antagonists. Toward selective targeting, we have developed the γ-secretase inhibitor-based prodrugs 13a and 15a as substrates for γ-glutamyltranspeptidase (γ-GT) and/or γ-glutamylcyclotransferase (γ-GCT) as well as aminopeptidase A (APA), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
(115 reference statements)
1
15
0
Order By: Relevance
“…Another most important and bewildering problem is that we observed a significant increase in myeloid differentiation after knock-down of the Notch1 by shRNA, while no such effect was found in GSI mediated Notch 1 knock-down. As a member of hydrolytic enzyme families, DAPT can hydrolyze Notch binding protein to block the Notch signal, and is also considered to have the effect to down regulate the Notch1 expression at the mRNA level [ 24 ]. We speculate that there might be other influential factors in the differentiation of mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Another most important and bewildering problem is that we observed a significant increase in myeloid differentiation after knock-down of the Notch1 by shRNA, while no such effect was found in GSI mediated Notch 1 knock-down. As a member of hydrolytic enzyme families, DAPT can hydrolyze Notch binding protein to block the Notch signal, and is also considered to have the effect to down regulate the Notch1 expression at the mRNA level [ 24 ]. We speculate that there might be other influential factors in the differentiation of mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent approach, 162 synthetic or non-GSI biological molecules, such as bioengineered antibodies or antagonists. 162,163 No large multicenter phase III clinical trial has yet been initiated, therefore it is premature to foresee the future of these therapeutics, but the tolerability profile has been shown to be acceptable (at least in the context of cancer) in early phase I/II clinical trials.…”
mentioning
confidence: 99%
“…The protein Notch-1 has a representative receptor in the Notch protein family, and its downstream intracellular domain is deemed a key target for therapy in various kidney diseases 22 . Studies have demonstrated that aberrant activation of the Notch-1 pathway has an important role in the processes associated with podocyte injury in DN 23 25 . The NICD translocates into the nucleus and associates with DNA-binding proteins to form a DNA-bound transcription factor that can also activate expression of target genes 22 , 26 .…”
Section: Discussionmentioning
confidence: 99%